2011
DOI: 10.1007/s10342-011-0488-2
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression models for human-caused wildfire risk estimation: analysing the effect of the spatial accuracy in fire occurrence data

Abstract: About 90% of the wildland fires occurred in Southern Europe are caused by human activities. In spite of these figures, the human factor hardly ever appears in the definition of operational fire risk systems due to the difficulty of characterising it. This paper describes two spatially explicit models that predict the probability of fire occurrence due to human causes for their integration into a comprehensive fire risk-mapping methodology. A logistic regression technique at 1 9 1 km grid resolution has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 24 publications
1
40
0
1
Order By: Relevance
“…Outdoor recreational activities (Romero-Calcerrada et al 2008Vilar del Hoyo et al 2011) have been found to be associated with a higher probability of HCF ignitions. Proximity to campgrounds (Pew and Larsen 2001;Gonzalez-Olabarria et al 2011;Mann et al 2016) or fishing areas (Chang et al 2013;Sitanggang et al 2013) is often related to negligent or careless fires.…”
Section: Predictors For Long-term Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Outdoor recreational activities (Romero-Calcerrada et al 2008Vilar del Hoyo et al 2011) have been found to be associated with a higher probability of HCF ignitions. Proximity to campgrounds (Pew and Larsen 2001;Gonzalez-Olabarria et al 2011;Mann et al 2016) or fishing areas (Chang et al 2013;Sitanggang et al 2013) is often related to negligent or careless fires.…”
Section: Predictors For Long-term Studiesmentioning
confidence: 99%
“…Urban, forest and agricultural land uses coexist and intermix in these anthropic landscapes, and interfaces between them seem to favour HCF occurrence in those models that have taken them into consideration (63 interface out of 230 land-use variables) (Vilar del Hoyo et al 2011;Faivre et al 2014;Duane et al 2015;Mishra et al 2016;Modugno et al 2016;Rodrigues et al 2016). Configuration metrics have not been applied as extensively (only 13 variables) as composition or land-cover variables, but fire-prone landscapes often present high fragmentation (Martínez et al 2009;Ruiz-Mirazo et al 2012;Martínez-Fernández et al 2013) and non-complex shapes linked to the artificial boundaries set by humans (Henry and Yool 2004;Gralewicz et al 2012b;Costafreda-Aumedes et al 2013).…”
Section: Predictors For Long-term Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ordinal recovery classes (Table 1) were expressed as binary variables by attributing the value "1" if pine woodland had recovered to its pre-fire state and the value "0" if not. Binary logistic regression was then performed to predict the value of a response variable (reference category "recovered" in this study) from the values of a set of environmental explanatory variables [47,55,56]. A regression analysis was performed by testing the best model applying the BIC criterion in the "bestglm" package in R [52] including the following continuous variables as predictors: "altitude," "slope," "aspect," "solar radiation," "distance from unburned sites," "distance from unburned P. brutia forest," and the categorical variables "soil depth," "bedrock type,"…”
Section: Logistic Regressionmentioning
confidence: 99%
“…In Spain, the increase in forest fires incidence is partly explained by climate change as well as socio-economic transformation in rural areas. Climate change has resulted in higher mean temperature and lower relative humidity, whilst socio-economic change has lead to the abandonment of farms, resulting in an increase and an unusual accumulation of forest fuels (Villar del Hoyo et al, 2011). The accumulation of forest fuels and the higher temperature can potentially lead to the outbreak of wildfires.…”
Section: Introductionmentioning
confidence: 99%